2015
DOI: 10.1002/ange.201412052
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Coordinative Unsaturation and Local Environment of Ti3+ Sites in an Activated High‐Yield Ziegler–Natta Catalyst

Abstract: Cl hyperfine and nuclear-quadrupole tensors with DFT-computed values suggests that the dominant EPR-active Ti 3+ species is located on MgCl 2 (110) surfaces (or equivalent MgCl 2 terminations with tetra-coordinated Mg). O 2 reactivity tests show that af raction of these Ti sites is chemically accessible,a ni mportant result in view of the search for the true catalyst active site in olefin polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…[31][32][33] "Superactive" catalysts upports have been prepared from molecular adducts between MgCl 2 and alcohols. [34,35] However,aclear correlation between the synthesis variables and the properties of the catalyst at the nanoscale is still missing.Since the 1980s, [36,37] ZN catalysts have been traditionally investigated by meanso fm olecular mechanics and quantummechanical computations aimed at identifying possible reaction mechanisms for olefin polymerization on what were supposed to be the most stable MgCl 2 surfaces in the presence of LBs and Ti x Cl 4Àx .I nt he last decade, the application of DFT and DFT methods including dispersion (DFT-D) to elucidatet he energeticso ft he interaction and the local structures of TiCl 4 (or Ti x Cl 3x )a nd the LB at these surfaces [25,[38][39][40][41][42][43][44][45][46] substantially re- [a] Dr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] "Superactive" catalysts upports have been prepared from molecular adducts between MgCl 2 and alcohols. [34,35] However,aclear correlation between the synthesis variables and the properties of the catalyst at the nanoscale is still missing.Since the 1980s, [36,37] ZN catalysts have been traditionally investigated by meanso fm olecular mechanics and quantummechanical computations aimed at identifying possible reaction mechanisms for olefin polymerization on what were supposed to be the most stable MgCl 2 surfaces in the presence of LBs and Ti x Cl 4Àx .I nt he last decade, the application of DFT and DFT methods including dispersion (DFT-D) to elucidatet he energeticso ft he interaction and the local structures of TiCl 4 (or Ti x Cl 3x )a nd the LB at these surfaces [25,[38][39][40][41][42][43][44][45][46] substantially re- [a] Dr.…”
mentioning
confidence: 99%
“…Since the 1980s, [36,37] ZN catalysts have been traditionally investigated by meanso fm olecular mechanics and quantummechanical computations aimed at identifying possible reaction mechanisms for olefin polymerization on what were supposed to be the most stable MgCl 2 surfaces in the presence of LBs and Ti x Cl 4Àx .I nt he last decade, the application of DFT and DFT methods including dispersion (DFT-D) to elucidatet he energeticso ft he interaction and the local structures of TiCl 4 (or Ti x Cl 3x )a nd the LB at these surfaces [25,[38][39][40][41][42][43][44][45][46] substantially re-newed the seminalv ision of catalysis on MgCl 2 .R ecent simulations performed on clusters of different sizes and morphologies [41,42] demonstrated that the relative stabilities of the MgCl 2 surfaces drastically change in the presence of donors. This holds for several small donor molecules (e.g.,H 2 O, [44] NH 3 , [44] methanol, [42,44] ethanol [44] ), as well as for the industrially employed donors.…”
mentioning
confidence: 99%
“…2a), that could be assigned to Ti(III), Mn(II) and some organic species. [30] While these spectral features remain unchanged after impregnation of the sample with a TEKPol/TCE solution, no EPR signal corresponding to TEKPol could be detected, pointing to the disappearance of the DNP polarizing agent upon impregnation of this material (Fig. 2b).…”
mentioning
confidence: 97%
“…For the first step, we selected, a Ziegler-Natta propylene polymerization pre-catalyst (ZN-EB) [30], based on TiCl4/MgCl2/EB with ethyl benzoate (EB) as the internal donor, because earlier unreported studies from our group showed the absence of DNP enhancements in these sample using classical formulation, namely 16 mM solution of TEKPol in TCE (TEKPol/TCE). [9] EPR studies of ZN-EB indicated the presence of surface radicals with g-factors 1.76-2.17 ( Fig.…”
mentioning
confidence: 99%
“…For this purpose, several experimental [29][30][31][32][33][34][35] and computational 13,15,[36][37][38][39][40][41][42][43][44][45][46] studies were performed. Many features of the catalyst, as the structure of the precatalyst, the activation process, the oxidation state(s) of the active titanium species during the polymerization process were investigated; notwithstanding, there are still several open questions.…”
mentioning
confidence: 99%